حکمران کی برطرفی کے بنیادی اصول : اہلِ کتاب اور اسلام کی تعلیمات کا تقابلی جائزہ: Fundamental Principles of the Removal of a Rulers: A Comparative Analysis of the Doctrines of Ahl-e-Kitab and Islam - Usman Shafiq (International Research Journal of Arabic and Islamic Studies, 2024)
The question of ruler’s removal has long occupied a significant place in religious and political thought. Both Ahl-e-Kitab and Islam stress the sanctity of political order and prohibit rebellion against legitimate authority, permitting removal only under exceptional and well-defined circumstances. In the Judaic and Christian traditions, the removal of rulers was historically regarded as the prerogative of religious or elite authorities rather than the general populace, as reflected in biblical accounts and medieval ecclesiastical practices. Similarly, Islamic teachings strictly forbid violent insurrection, even in cases of tyranny or injustice, while acknowledging the possibility of ruler removal through legitimate, collective, and lawful procedures. Nevertheless, the Qur’an, the Sunnah, and the juristic legacy of early Muslim scholars provide a more systematic and comprehensive framework, outlining both the principles of obedience and the legitimate grounds for removal. Hence, while the two traditions converge on fundamental principles, Islam offers a more detailed, structured, and nuanced perspective on the matter.